Model for microbiologically influenced corrosion potential assessment for the oil and gas industry. (4th July 2018) - Taleb-Berrouane, Mohammed; Khan, Faisal; Hawboldt, Kelly; Eckert, Richard; Skovhus, Torben Lund
ABSTRACT: Corrosion is one of the major causes of failure in onshore and offshore oil and gas operations. Microbiologically influenced corrosion (MIC) is inherently more complex to predict, detect and measure because, for instance, the presence of biofilm and/or bacterial products is not sufficient to indicate active microbiological corrosion. The major challenge for current MIC models is to correlate factors that influence corrosion (i.e. chemical, physical, biological and molecular variables) with the potential of having MIC. Previous work has proposed the potential for MIC as a simple product of multiple factors, without fully considering the synergy or the interference among the factors. The present work proposes a network-based approach to analyse and predict MIC potential considering the complex interactions among a total of 60 influencing factors and 20 screening parameters. The proposed model has the ability to capture the complex interdependences and the synergic interactions of the factors used to assess MIC potential and uses an object-oriented approach based on a Bayesian Network. The model has been tested and verified using real data from a pipeline leakage incident that was a result of MIC. The proposed model constitutes a significant step in deepening the understanding of when MIC occurs and its predictability. List of acronyms: APB: acid producing bacteria; Aw: water activity; BN: Bayesian network; MIC: microbiologically influenced corrosion; MMMs: molecular microbiological methods; NRB: nitrate-reducing bacteria; OOBN: object-oriented Bayesian network; PWRI: produced water re-injection; SPs: screening parameters; SRB: sulphate-reducing bacteria; SRPs: sulphate-reducing prokaryotes; TDSs: total dissolved solids